The Code Analysis of ‘Post-Apocalyptic Era’ Movies: Take Mad Max: Fury Road as an Example - Liu, Yuhao (Transactions on Social Science, Education and Humanities Research, 2024)
In the 88th Academy Awards, directed by George Miller, a "wasteland" theme film "Mad Max 4: Fury Road" is the world’s most recognized female theme film. 50% of film history is one of the films in the explosive stage. After it won the Oscar six awards, it has become a "wasteland" theme film’s new benchmark. Through semiotics and the Bible, this paper deconstructs the image codes in movies. Based on the symbolic interactionism theory, this paper analyses the character behaviour, identity construction and prop application in the Christian symbol system and combs and deconstructs it, trying to explore the symbolic metaphors in movies and reflect on the artistic value and ideological connotation contained in movies.